1998
DOI: 10.1080/00016359850142853
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged pacifier-sucking and use of a nursing bottle at night: possible risk factors for dental caries in children

Abstract: At the baseline of this cohort study we determined risk factors for colonization of oral lactobacilli and candida in a group of children (n = 166) whose mean age was 2.5 years. The results showed that pacifier-sucking and the use of a nursing bottle at night increase the occurrence of both salivary lactobacilli and candida. In the present study these children were followed for 2 years, and the progression of caries was recorded with particular reference to the etiologic factors measured before. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…Prolonged bottle feeding, bottle feeding on demand, use of comforters and the habit of sleeping beside the mother have all been shown to be associated with caries experience in the past. 21,37,[42][43][44][45][46][47] Results of this study also suggested that the habit of sleeping beside the mother and the use of comforters were independently associated with caries prevalence.…”
Section: Discussionmentioning
confidence: 86%
“…Prolonged bottle feeding, bottle feeding on demand, use of comforters and the habit of sleeping beside the mother have all been shown to be associated with caries experience in the past. 21,37,[42][43][44][45][46][47] Results of this study also suggested that the habit of sleeping beside the mother and the use of comforters were independently associated with caries prevalence.…”
Section: Discussionmentioning
confidence: 86%
“…The association between certain nonnutritive suction habits, particularly pacifier use, and the development of dental caries has been documented in diverse studies [Ollila et al, 1998;Levine, 1999]. There are several possible mechanisms through which pacifier use favors dental caries development.…”
Section: Discussionmentioning
confidence: 99%
“…Ollila et al [1998] studied the effect of pacifier use on dental caries in a group of 166 preschool children. The authors reached similar conclusions to those of our group, showing an association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations